Determinacion de glucosa en las mujeres integrantes del club de madres de Huanchaco - Huanchaco. enero 2011” - Castillo Salirrosas, Rider Antonio (2012)
In our research it was determined the plasma glucose levels in adult women members of the club of mothers of Huanchaco. To carry out this work, proceeding to take blood sample from a population, for which we chose the population of mothers' club of Huanchaco, women between 21 and 80 years of age. The results were handled using tables and graphs, as follows: 83.7% normal levels of blood glucose, decreased 7% and the remaining 9.3% of plasma glucose increased. So we can say that the population is mostly apparently healthy, being in the same way a result of relatively high blood glucose levels, which indicates predisposition to diabetes. We proceeded to the customized delivery of the results of plasma glucose of each patient, providing information and guidance necessary to maintain health status in patients with good results, and restore the state of health, in those patients who achieved plasma levels of altered glucose